PENGARUH MODEL DAN STRATEGI PELATIHAN TERHADAP MUTU PELAYANAN DOSEN - Efendi Napitupulu (Jurnal Teknologi Pendidikan (JTP), 2012)
The objectives of this research were to determine the effects of model and training strategy on lecturer service quality. Two models of lecturer instructional quality improvement were applied in this research: the quality oriented and conventional models, while training strategy was divided into cooperative and indivualistic strategy. This research was experimental design used was the 2x2 factorial design. A questionnaire was administered to collect data on lecturer service quality consisting of 58 items (r= .98). ANAVA and t-test was used to analyze the data, t-test were used to analyze the differences between experimental groups at .05 level of significance. The result of this study indicated that (1) In general it can be concluded, that the quality of the lecturer service quality in the classroom, the quality oriented model was better than that of the conventional model; (2) In the cooperative strategy, the quality- oriented model was better than the conventional model; (3) In the individual strategy, the quality-orientedmodel was better than the conventional model, (4) there was no interaction effects between lecturer instuction quality model and training strategy on lecturer service quality. From the research findings it can be concluded that: The service quality of the trained lecturer which was quality-oriented model was better than that of the conventional model, whichever the strategy was used to improved the instructional quality of the lecturer. In other words, training to improved the lecturer instructional quality in the classroom, the model which stressed quality was better than model which did not stres quality.